2014
DOI: 10.5194/hessd-11-13311-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Notes on the estimation of resistance to flow during flood wave propagation

Abstract: Abstract. The paper discusses methods of expressing and evaluating resistance to flow in an unsteady flow. Following meaningful trends in hydrological sciences, the paper suggests abandoning, where possible, resistance coefficients in favour of physically based variables such as shear stress and friction velocity. Consequently, an acknowledged method of friction velocity evaluation based on the relations derived from flow equations is examined. The paper presents both a theoretical discussion of various aspect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…grain roughness, form drag due to bedforms and channel geometry, vegetation resistance, as well as added fluid resistance due to sediment transport) into a single roughness parameter (Trieste and Jarrett, ; Lumbroso and Gaume, ). Field guides and empirical equations have been developed to facilitate more accurate estimates of Manning's n , but these often perform poorly in small mountain streams (Marcus et al , ; Smith et al , ; Ferguson, ; Mrokowska et al , ) as evidenced by the wide range of Manning's n values estimated by these different methods for our reach (0.03 to 0.13, excluding XS7).…”
Section: Discussionmentioning
confidence: 99%
“…grain roughness, form drag due to bedforms and channel geometry, vegetation resistance, as well as added fluid resistance due to sediment transport) into a single roughness parameter (Trieste and Jarrett, ; Lumbroso and Gaume, ). Field guides and empirical equations have been developed to facilitate more accurate estimates of Manning's n , but these often perform poorly in small mountain streams (Marcus et al , ; Smith et al , ; Ferguson, ; Mrokowska et al , ) as evidenced by the wide range of Manning's n values estimated by these different methods for our reach (0.03 to 0.13, excluding XS7).…”
Section: Discussionmentioning
confidence: 99%
“…The other most classical example is the hysteretic relation between water level and discharge during backwater events (Herschy, 2009;Hidayat et al, 2011). As has been well documented, single-parameter rating curves developed for particular hydrometric stations fail to reflect the real discharge under unsteady flow occurring during backwaters or flood propagation waves (Hidayat et al, 2011;Mrokowska et al, 2014;Petersen-Overleir, 2006;Rowiński et al, 2000). To compare, the studies of Moog and Whiting (1998) have shown the hysteresis between river discharge and bed load transport, whereas Williams (1989) reported hysteresis between discharge and sediment concentration rates during flood events.…”
Section: Discussionmentioning
confidence: 99%